EVALUATION OF THE RESULTS OF TREATMENT PATIENTS WITH ACUTE CORONARY SYNDROM IN SELECTED HOSPITALS OF KRASNODAR REGION (PART OF THE RUSSIAN REGISTER RECORD-3) - S. A. RAFF; E. D. KOSMACHEVA (Кубанский научный медицинский вестник, 2017)
Demonstrated the results of prospective study of 661 patients were admitted in 17 hospitals of Krasnodar region with a diagnosis of acute coronary syndrome (ACS). Identify risk factors for cardiovascular diseases and medical history data were analyzed. The evaluation of diagnostic and therapeutic measures at different stages of care. Conclusions. Delivery times of patients with ACS in the hospital is not optimal. Outpatient therapy is insufficiently even after PCI and CABG. In the treatment of the hospital patients receive inadequate doses of antiplatelet agents. The proportion of patients who received reperfusion therapy should be increased. The use of invasive procedures for the diagnosis and treatment of acute coronary syndrome significantly improve outcomes and prognosis, with a low level of complications.